THE TEACHER'S ROLE IN PROJECT TEACHING - SMERINGAIOVA, Anna (Trends in education, 2019)
The article describes the process of preparation and application of the project method in the subject "Analysis of Operation Parameters of Technological Equipment". The subject is focused on determining the technical condition of machines using non-destructive diagnostics methods. Several methods and forms of university education were used in the application of project teaching. This is an analysis of the role of the teacher, as the assigner of tasks and the coordinator of the project team solution process. From the teacher's point of view, the achieved results of the work and the overall course of teaching are evaluated.
Keywords: project method; cooperative teaching; role of teacher